The Psychological Dynamics of Solastalgia: A Reflective Foundation for Indonesian Social Science and Humanities Scholars - Pelupessy, Muhammad Kashai Ramdhani; Tihurua, Ode Zulkarnain Sahji (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2025)
Solastalgia is a form of existential distress that emerges when individuals experience a rupture in their relationship with their dwelling due to drastic environmental changes. Despite its serious psychological implications, this phenomenon has not been widely discussed, particularly among scholars of social and human sciences, such as psychologists, anthropologists, and sociologists in Indonesia. Therefore, this article provides a reflective foundation by drawing on the phenomenologies of Heidegger and Husserl to focus on the meaning of place, self-identity, and emotional attachment. The dynamics of those three factors is what potentially contributes to the emergence of solastalgia. Based on a literature review, this article engages in a reflective discussion on: (1) how dwelling is perceived and understood by individuals; (2) findings regarding the disconnection between individuals and their dwellings; (3) the psychological dynamics of solastalgia; and (4) the urgency of solastalgia research in Indonesia. This study is expected to serve as a reflective point of departure for social and human sciences scholars in Indonesia—such as psychologists, anthropologists, and sociologists—who wish to investigate solastalgia in a deeper and more critical manner.